Cellulose nanofibers enable paraffin encapsulation and the formation of stable thermal regulation nanocomposites. (April 2017) - Li, Yuanyuan; Yu, Shun; Chen, Pan; Rojas, Ramiro; Hajian, Alireza; Berglund, Lars
Abstract: Non-leaking, green materials with high content of phase change materials (PCM) can conserve solar energy and contribute to a sustainable society. Here, paraffin was encapsulated by nanocellulose (CNF) through a pickering emulsion method, while simultaneously forming a composite material. The thermodynamic drive for phase separation was confirmed by molecular modeling. Particle formation was characterized by dynamic light scattering and they were processed into stable PCM/CNF composites in the form of PCM paper structures with favorable mechanical properties. The PCM composite was lightweight and showed a solid content of paraffin of more than 72 wt%. Morphology was characterized using FE-SEM. The thermal regulation function of the PCM composite was demonstrated in the form of a model roof under simulated sunlight. No obvious leakage was observed during heating/cooling cycles, as supported by DSC and SAXS data. The PCM composite can be extended to panels used in energy-efficient smart buildings with thermal regulation integrated in load-bearing structures. Graphical abstract: Highlights: CNF enabled paraffin encapsulation through an aqueous pickering emulsion method. The capsules formation and dispersion in CNF matrix are completed in one step. The thermodynamic drive for capsules formation was confirmed by molecular modeling. The PCM paper shows good thermal regulation and mechanical property without leakage. The PCM paper is a promising structural candidate for smart building applications.